Genetic and phenotypic basis of goat adaptability across agro-ecological zones: Implications for breeding and conservation - Kichamu, Nelly; Astuti, Putri Kusuma; Kusza, Szilvia (Acta Agraria Debreceniensis, 2026)
Goats are among the most adaptable livestock species that can survive in varied agro-ecological zones globally. This resilience is shaped by the interactions between genetic and phenotypic traits. This review assesses the available information on morphology, physiology, and molecular characteristics that enable them to adapt and their implication for breeding and conservation. Phenotypic characteristics, including variation in coat color, the type and density of hair, body size, skin color, and thermoregulation behavior, were observed to be measures of adaptation to heat, cold, and feed scarcity. The review also observed some key candidate genes at the molecular level, including HSP70, EPAS1, FGF5, and MC1R, among others, with pathways that are responsible for heat tolerance, hypoxia response, and metabolic efficiency. The link between environmental pressures and phenotypic variation is examined as a driver for genetic differentiation among local goat populations. Incorporating these phenotypic and genetic insights forms a basis for breeding strategies that are climate-resilient and for safeguarding adaptive genetic resources. This will ensure that goats stay productive and diverse over time, thereby contributing to food security and the current climate change.